Social assessment of miscanthus cultivation in Croatia: Assessing farmers' preferences and willingness to cultivate the crop - Nirvana A. Marting Vidaurre; Vanja Jurišić; Claudia Bieling; Elena Magenau; Moritz Wagner; Andreas Kiesel; Iris Lewandowski (GCB Bioenergy, 2023)
Abstract Social aspects of miscanthus cultivation have been investigated in a limited way in the scientific literature. Adopting existing frameworks for social life‐cycle assessment enables assessments to include numerous social aspects; however, the relevance of these aspects depends on the local context. This study aims to identify the most relevant social aspects from the farmers' perspective using a previously proposed framework for the assessment of the stakeholder ‘farmer’. It is based on a case study for miscanthus production in Sisak Moslavina in Croatia. The existence of abandoned lands in Croatia presents an opportunity for the cultivation of miscanthus as a potential source of biomass for the production of bio‐based materials and fuels. The study seeks to assess the feasibility of cultivating miscanthus in the region, taking into account potential challenges and opportunities, as well as farmers' willingness to adopt the crop, and to understand the reasons behind land abandonment. We conducted a survey among 44 farmers in the region and used a scoring method to identify the most relevant social aspects. The aspects most valued by the farmers were health and safety, access to water, land consolidation and rights, income and local employment, and food security. Responses to the question of whether they would adopt the crop highlight the importance of an established market, good trading conditions and profitability of cultivation. The survey also enabled an understanding of farmers' preferences with respect to the production conditions of crops. The farmers regarded the provision of subsidies as one of the main factors that render a crop attractive. Opportunities for the adoption of the miscanthus cultivation include high yields and low input requirements. Barriers include land conflicts and land availability. Despite the opportunities for miscanthus development in the region, there are important challenges to consider for successful implementation of the crop.